Levante popular da juventude brasileira: saímos do Facebook - Bernardini, Gleice [UNESP]; Gobbi, Maria Cristina [UNESP] (My University, 2013)
The paper studies the mobilization occurred in June 2013 in Brazil, initially under the banner of the Movement Free Pass, but without the existence of a lead, but multiple voices that alternate in search of social and economic change. The object of study is the communication made through social networks and their realization, or realization, the streets of major cities. The rallies demonstrate the power of communications media and a new phenomenon of talk, the use of social networks, now as uniting factor and not just a showcase of everyday life. The internet has become a new means of communication easy and free access, in addition to its fast dissipation data. Thus, the youth was used such technology to an uprising in the pursuit of social improvement of the cities where marches happened. Such a move still without an academic and social needs to be discussed so that, in addition to understood, can expand contributions to society, helping it in its claims. Was chosen as the site for the #causabrasil study and understanding of issues in which the public expresses dissatisfaction. The site performs an analysis with the combination of hastags a list of pre-registered and a list of terms used by different users of Facebook, Twitter, Instagram, Youtube and Google, through monitoring tool Seekr, and an infographic presents the main political demands of the population.

O artigo visa estudar o movimento ocorrido em junho de 2013 no Brasil, inicialmente sob a bandeira do Movimento Passe Livre, porém sem a existência de uma liderança, mas múltiplas vozes que se alternam na busca de mudanças sociais e econômicas. O objeto de estudo é a comunicação feita através das redes sociais e sua realização, ou concretização, nas ruas das principais cidades do país. As passeatas demonstram a força da comunicação midiática e de um novo fenômeno de conversação, o uso das redes sociais, agora como fator de união e não mais apenas como vitrine da vida cotidiana. A internet se tornou um novo meio de comunicação de fácil e livre acesso, além de sua rapidez na dissipação de dados. Desta forma, a juventude se utilizou de tal tecnologia para um levante na busca de melhorias sociais das cidades onde aconteceram as passeatas. Tal movimento ainda sem um estudo acadêmico e social deve ser debatido para que, além de entendido, possa ampliar as contribuições com a sociedade, auxiliando-a em suas reivindicações. Foi escolhido o site #causabrasil para o estudo e percepção das questões pela qual o público manifesta insatisfação. O site realiza uma análise com a combinação de uma lista de hastags pré-cadastradas e uma lista de diferentes termos utilizados por usuários do Facebook, Twitter, Instagram, Youtube e Google, através da ferramenta de monitoramento Seekr, e em um infográfico apresenta as principais bandeiras de luta da população.
Popular mobilization of brazilian youth: go out the Facebook
Keywords: Internet; Communication; Brazil; Youth; Social mobilization; Internet; Comunicação; Brasil; Juventude; Movimentos sociais